Step
*
1
1
1
1
1
of Lemma
iterate-rotate-rotate-by
1. n : ℕ
2. i : ℤ
3. ¬i < 1
4. 0 < i
5. rot(n)^i - 1 = rotate-by(n;i - 1) ∈ (ℕn ⟶ ℕn)
6. x : ℕn
7. n = 1 ∈ ℤ
⊢ (((x + (i - 1) rem 1) + (1 rem 1) rem 1) = ((x + (i - 1)) + 1 rem 1) ∈ ℤ)
⇒ (if (x + (i - 1) rem 1 =z 1 - 1) then 0 else (x + (i - 1) rem 1) + 1 fi 
   = ((x + (i - 1) rem 1) + (1 rem 1) rem 1)
   ∈ ℤ)
BY
{ (RWO "rem-1" 0⋅ THEN Auto) }
Latex:
Latex:
1.  n  :  \mBbbN{}
2.  i  :  \mBbbZ{}
3.  \mneg{}i  <  1
4.  0  <  i
5.  rot(n)\^{}i  -  1  =  rotate-by(n;i  -  1)
6.  x  :  \mBbbN{}n
7.  n  =  1
\mvdash{}  (((x  +  (i  -  1)  rem  1)  +  (1  rem  1)  rem  1)  =  ((x  +  (i  -  1))  +  1  rem  1))
{}\mRightarrow{}  (if  (x  +  (i  -  1)  rem  1  =\msubz{}  1  -  1)  then  0  else  (x  +  (i  -  1)  rem  1)  +  1  fi 
      =  ((x  +  (i  -  1)  rem  1)  +  (1  rem  1)  rem  1))
By
Latex:
(RWO  "rem-1"  0\mcdot{}  THEN  Auto)
Home
Index